2015
DOI: 10.1118/1.4905048
|View full text |Cite
|
Sign up to set email alerts
|

Suitability of poroelastic and viscoelastic mechanical models for high and low frequency MR elastography

Abstract: Purpose: Descriptions of the structure of brain tissue as a porous cellular matrix support application of a poroelastic (PE) mechanical model which includes both solid and fluid phases. However, the majority of brain magnetic resonance elastography (MRE) studies use a single phase viscoelastic (VE) model to describe brain tissue behavior, in part due to availability of relatively simple direct inversion strategies for mechanical property estimation. A notable exception is low frequency intrinsic actuation MRE,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
59
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(62 citation statements)
references
References 71 publications
3
59
0
Order By: Relevance
“…Viscoelasticity, represented by the complex shear modulus, is the most widely used material model for inversion in brain MRE, though this model for attenuation may be inappropriate in SGM. Alternative material models, including Rayleigh damping [McGarry and Van Houten, 2008; Van Houten et al, 2011] and poroelasticity [McGarry et al, 2015; Pattison et al, 2014], may better explain attenuation in SGM structures and have shown promise in brain MRE [Johnson et al, 2013b; Weaver et al, 2012]. And, while GM is generally considered to be isotropic [Prange and Margulies, 2002; Velardi et al, 2006], the structure of SGM includes axonal pathways and may benefit from a direction-dependent material model as has been used in WM [Anderson et al, 2016; Romano et al, 2012].…”
Section: Discussionmentioning
confidence: 99%
“…Viscoelasticity, represented by the complex shear modulus, is the most widely used material model for inversion in brain MRE, though this model for attenuation may be inappropriate in SGM. Alternative material models, including Rayleigh damping [McGarry and Van Houten, 2008; Van Houten et al, 2011] and poroelasticity [McGarry et al, 2015; Pattison et al, 2014], may better explain attenuation in SGM structures and have shown promise in brain MRE [Johnson et al, 2013b; Weaver et al, 2012]. And, while GM is generally considered to be isotropic [Prange and Margulies, 2002; Velardi et al, 2006], the structure of SGM includes axonal pathways and may benefit from a direction-dependent material model as has been used in WM [Anderson et al, 2016; Romano et al, 2012].…”
Section: Discussionmentioning
confidence: 99%
“…However, a comprehensive model that can describe tissue biomechanics at a wide range of frequencies is still unknown. For example, using magnetic resonant elastography (MRE) the study in [13] shows that due to biphasic nature of tissue a single constitutive model cannot simultaneously explain tissue behavior at different frequency ranges. Hence, a unified approach to separate the dynamics of the two phases, i.e., a viscoelastic deformable solid response and a hydraulic fluid motion, in tissue-like materials is still an open problem [14], [15].…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, NLI, which refers to a class of iterative schemes, recovers a set of unknown properties by minimizing an objective function defining the least-squares difference between the computed displacement field and measured data, and functions well across a wider range of frequencies than DI [28], however, at the expense of significantly increased computational cost. NLI has been demonstrated in MRE by Van Houten et.…”
Section: Introductionmentioning
confidence: 99%
“…Selecting an appropriate model is important to avoid model-data mismatch [31], and NLI has been extended and modified to incorporate other mechanical models, including viscoelastic [32], incompressible [33], Rayleigh damped [34], [35] and poroelastic [36], [28] governing equations. Computing one GN update involves calculation of a Jacobian matrix that requires one forward solution per unknown property value, and a costly inversion of a large, full Hessian matrix.…”
Section: Introductionmentioning
confidence: 99%